Nanostructured materials and nanotechnology VII : a collection of papers presented at the 37th International Conference on Advanced Ceramics and Composites, January 27-February 1, 2013, Daytona Beach, Florida - Mathur, Sanjay; Hernandez-Ramirez, Francisco; Kirihara, Soshu; Wijaja, Sujanto (Ceramic engineering and science proceedings ;, 2014)
Ceramic Engineering and Science Proceedings Volume 34, Issue 7 - Nanostructured Materials andNanotechnology VII A collection of 16 papers from The American Ceramic Society's 37th International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 27-February 1, 2013. This issue includes papers presented in the 7th InternationalSymposium on Nanostructured Materials and Nanotechnology (Symposium 7) andNanomaterials for Sensing Applications symposia (Focused Session 3).